ANALISIS PENJUALAN, HARGA POKOK PENJUALAN, DAN BEBAN USAHA TERHADAP LABA USAHA PADA PERUSAHAAN MANUFAKTUR BEI - Nugeraheni, Cahya Kusuma; Winarko, Sigit Puji; Zaman, Badrus (Universitas Nusantara PGRI Kediri, 2023)
Sales, Cost of Goods Sold (HPP), and Operating Expenses are some of the important factors that require attention considering that they can affect Operating Profit. The following research aims to analyze the influence of Sales, HPP, and Operating Expenses on Operating Income. This research was conducted at a manufacturing company in the food and beverage sector which is listed on the Indonesia Stock Exchange (IDX) in 2022. Testing the hypothesis used the multiple linear regression analysis methods with the T-test, F-test, and coefficient of determination (R2). The population in the following research is manufacturing companies in the food and beverage sector which are listed on the IDX in 2022. The sample selection used a purposive sampling technique, so in the following study, 40 of the 46 population of companies were found as research samples listed on the IDX in 2022. The research results explain that sales have a significant positive effect on net income while HPP and Operating Expenses have a significant negative effect on net income.